Pendidikan Islam dan Dakwah sebagai Landasan Etis Pelayanan Publik Melampaui Rasionalitas Birokrasi - Beni Pramula; Rahmat Salam; Siti Nuri Nurhaidah; Fikri Yasin; Nabiel Al Musawa (Jurnal Studi Pendidikan Agama Islam, 2025)
This study examined the limitations of bureaucratic rationality in public service delivery and explored how Islamic education and da’wah functioned as ethical foundations for human- centred public services. The research was conducted using a qualitative approach grounded in document analysis, normative Islamic texts, and selected empirical studies on public administration and religious ethics. Data were analysed thematically to identify points of tension between procedural rationality, efficiency-oriented governance, and human values such as dignity, empathy, and moral responsibility. The study found that bureaucratic rationality, while JSPAI effective in ensuring order, predictability, and accountability, often reduced citizens to administrative objects and neglected lived human experiences. Islamic education was shown to cultivate ethical awareness, moral reasoning, and character formation, while da’wah operated as a communicative and transformative process that internalised values of justice, compassion, and public responsibility among service providers. The results indicate that the integration of Islamic educational values and da’wah ethics reorients public services towards human-centred practices, where rules are balanced with moral judgement and social sensitivity. The study concludes that Islamic education and da’wah provide a viable ethical framework for humanising public service delivery without undermining bureaucratic structure. This approach offers an alternative paradigm in which efficiency and regulation coexist with ethical consciousness, empathy, and social justice. The findings contribute to international discussions on public administration, ethics, and religion by proposing a culturally grounded yet universally relevant model of human-centred public services.